Expression of nitric oxide synthases from photosynthetic microorganisms improves growth and stress tolerance in E. coli - Correa Aragunde, Maria Natalia (2020)
Nitric oxide synthase (NOS) catalyzes the oxidation of the substrate L-Arginine (Arg) to produce citrulline and nitric oxide (NO). We have characterized NOS from two photosynthetic microorganisms: the NOS from the alga Ostreococcus tauri (OtNOS) and the cyanobacteria Synechococcus PCC 7335 (SyNOS). OtNOS and SyNOS possess distinct biochemical properties. OtNOS is a canonical NOS similar to animal NOS with an ultrafast NO producing activity. On the contrary, an extra globin domain present in SyNOS enzyme oxidizes over 70 % of the NO-produced to nitrate (NO3-). Here we describethe expression of recombinant OtNOS and SyNOS in Escherichia coli BL12 strain and analyze bacterial growth and tolerance to nitrosative stress. Results show that the E. coli cultures expressing OtNOS and SyNOS reach a higher OD at the exponential phase with respect to bacteria transformed with the empty vector (EV). This result correlates with higher NOS protein levels assayed by immunoblot, total protein and nitrate content in NOS recombinant strain cultures. Moreover, the expression of SyNOS and at less extent of OtNOS confers the ability to grow in minimal medium with Arg as a sole N source (and plenty C-source), suggesting that NOS enzymes are active in E. coli. The high NO producing activity reported in OtNOS correlates with the flavohemoglobin hmp induction in E. coli strain expressing OtNOS, suggesting that this strain senses nitrosative stress. Furthermore, nitrosative stress generated by the addition of 1 mM of the NO donor sodium nitroprusside (SNP) reduced growth rate (0.4-fold respect to no SNP addition) in bacterial culture expressing EV. However, the expression of recombinant OtNOS and at less extent SyNOS, attenuated SNP toxicity (0.8- and 0.6-fold, respectively, compared to no SNP addition). E. coli does not synthesize the major NOS cofactor tetrahydrobiopterin (BH4). Bioinformatics tools and ligand docking analysis were used to provide evidence supporting tetrahydromonapterin (MH4) as a possible pterin cofactor required for NOS catalytic activity in E. coli. These results open an exciting new window about the versatility of pterin cofactor working in the different NOSs dispersed in distant organisms along the life tree. In summary, our results show that NOS from photosynthetic microorganisms increases the growth and confers nitrosative stress tolerance in E. coli. Supported by AGENCIA, CONICET and UNMdP